2010
DOI: 10.1186/1471-2393-10-87
|View full text |Cite
|
Sign up to set email alerts
|

All Our Babies Cohort Study: recruitment of a cohort to predict women at risk of preterm birth through the examination of gene expression profiles and the environment

Abstract: BackgroundPreterm birth is the leading cause of perinatal morbidity and mortality. Risk factors for preterm birth include a personal or familial history of preterm delivery, ethnicity and low socioeconomic status yet the ability to predict preterm delivery before the onset of preterm labour evades clinical practice. Evidence suggests that genetics may play a role in the multi-factorial pathophysiology of preterm birth. The All Our Babies Study is an on-going community based longitudinal cohort study that was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 45 publications
1
57
0
Order By: Relevance
“…The AOB cohort is well-educated and has above-average affluence, and is comparable to the target population of women who plan to become pregnant and parent in Canada [55,56]. Women who experienced interpersonal violence were more likely to have lower socioeconomic status, single, Caucasian, and Canadian born, compared to women with no reported experiences of interpersonal violence.…”
Section: Resultsmentioning
confidence: 99%
“…The AOB cohort is well-educated and has above-average affluence, and is comparable to the target population of women who plan to become pregnant and parent in Canada [55,56]. Women who experienced interpersonal violence were more likely to have lower socioeconomic status, single, Caucasian, and Canadian born, compared to women with no reported experiences of interpersonal violence.…”
Section: Resultsmentioning
confidence: 99%
“…The All Our Babies Cohort Study 103 , currently enrolling subjects in Alberta, Canada, is taking a fetal personalized medicine approach to understanding preterm birth by prospectively collecting maternal blood RNA and examining environmental factors. All of these investigations use comparative microarray analyses to identify new biomarkers and potential avenues for intervention.…”
Section: Advances In Analyzing the Fetal Transcriptomementioning
confidence: 99%
“…The Lifeways study was one of the first to show that general practitioner-reported wheeze or asthma (52) Czech Republic 7577 1994 x Devereux et al (53) UK 1400 1997 x x Drouillet et al (54) France 1900 2003 x x x x Dubois et al (55) Canada 1450 1998 x x Eggesbo et al (56) Norway 2500 2003 x x x Emanuel et al (57) UK 3076 1958 x Gorden-Larsen et al (58) USA 14 706 1995 x Gracie et al (59) Canada 3388 2008 x x Grandjean et al (60) Faroe Islands 1022 1986 x x x x Guldner et al (61) France 4000 2002 x x Guxens et al (62) Spain 3768 1997 x x x x x Grazuleviciene et al (63) Lithuania 4405 2007 x Hawkes et al (64) Ireland 2185 2008 x Hawkins et al (65) UK 13 113 2000 x Hill et al (66) Wales 420 2009 x x Hryhorczuk et al (67) Ukraine 4510 1992 x x x Hui et al (68) Hong Kong 8327 1997 x x Hunt et al (69) Canada 521 1981 x x Inskip et al (70) UK 3159 1998 x x Jaddoe et al (71) Netherlands 10 000 2002 x Jedrychowski et al (72) Poland 432 2000 x x Kaplowitz et al (73) UK 224 1986 x x Karvonen et al (74) Finland 442 2002 x x x x Katier et al (75) Netherlands 2500 (95) Germany 2000 2011 x x x x Richiardi et al (96) Italy 7500 2005 x x x x Schaefer-Graf et al (97) Germany 324 1995 † x x Sekine et al (98) Japan 8941 1992 x x Skalkidou et al (99) Sweden 580 2009 x x Tsuchiya et al (100) Japan 1260 2007 x x van Eijsden et al (101) The Netherlands 6161 2003 x x x x Vandentorren et al (102) France 20 000 2011 x x x Vecchi Brumatti et al (103) Italy 900 when the child averaged 3 years was inversely associated with maternal fruit and vegetable and fish consumption during pregnancy (1...…”
Section: Dietary Patterns and Risk Of Childhood Wheezing Or Asthmamentioning
confidence: 99%